1988
DOI: 10.1182/blood.v71.5.1402.bloodjournal7151402
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of refractoriness and HLA-alloimmunization using filtered blood products

Abstract: Depletion of leukocytes from all blood products may decrease the incidence of alloimmunization to HLA antigens present on the white cells and thus delay the onset of refractoriness to random donor platelet support. In order to test this hypothesis, 54 patients with hematologic malignancy or marrow aplasia were entered on a prospective randomized trial using cotton-wool filtration as a method of leukocyte depletion of red cell and platelet concentrates. Forty patients were considered evaluable; 20 patients rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(75 citation statements)
references
References 0 publications
3
71
0
1
Order By: Relevance
“…Our estimates of PRCA incidence are similar to the previously reported ones (Sniecinski et al, 1988), which are distinctly lower than 29-30% recently quoted in the setting of major/bidirectional ABO mismatch in RIC transplantation (Bolan et al, 2001;Worel et al, 2003). Few reports specify reticulocyte counts required for the diagnosis of PRCA, or define the interval to expected erythroid recovery after transplantation; thus the lack of standard diagnostic criteria may preclude comparisons with other reports.…”
Section: Discussionsupporting
confidence: 83%
“…Our estimates of PRCA incidence are similar to the previously reported ones (Sniecinski et al, 1988), which are distinctly lower than 29-30% recently quoted in the setting of major/bidirectional ABO mismatch in RIC transplantation (Bolan et al, 2001;Worel et al, 2003). Few reports specify reticulocyte counts required for the diagnosis of PRCA, or define the interval to expected erythroid recovery after transplantation; thus the lack of standard diagnostic criteria may preclude comparisons with other reports.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies of AML patients receiving induction chemotherapy examined the effect of leucoreduction on the incidence of alloimmunization. The incidence dropped from 48% to 16% in one study (Murphy et al, 1986), from 50% to 15% in another (Sniecinski et al, 1988), and from 45% to 17-21% in the TRAP Study (Slichter, 1997). The TRAP study also showed no difference in the rate of alloimmunization between leucoreduced single-donor (i.e.…”
Section: Immune Componentmentioning
confidence: 99%
“…Cell separation is a key process involved in leukocyte removal from blood cells for transfusion [1][2][3][4][5] and isolation of stem cells from peripheral and umbilical cord blood. 6,7 Polyurethane foam membranes [1][2][3]6,7 and nonwoven fabrics, 4 with pore sizes of 5-20 m, have been used as separation membranes for blood cells. The surfaces of these membranes are generally modified by grafting 6,7 or coating 4,5 with biocompatible polymers, to improve the hemocompatibility and control the hydrophilic-hydrophobic properties of the surface of the membranes.…”
Section: Introductionmentioning
confidence: 99%